Implementation of HMI (Islamic Student Association) Organizational Education in Creating Innovative and Moral Students at the Commissariat of the Faculty of Social Sciences, UIN Sumatera Utara - M. Ali Akbar Siregar; Sori Monang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
As a result of the development of internet access which has an impact on moral behavior, many generations are easily influenced by negative behavior in their social environment, the moral generation of Indonesia in modern times faces many significant challenges. Consequently, the objectives of this study are to: (1) Determine the Implementation of Innovative and Moral Organizational Education; (2) Identify the Factors Supporting and Hindering the Implementation of Innovative and Moral Organizational Education; and (3) Assessing the Impact of Implementing Innovative and Moral Organizational Education. This research uses qualitative research, which provides descriptive data in the form of written or spoken words from individuals based on observed behavior. Data collection techniques involve interviews, observation, and documentation. While data analysis uses Miles and Huberman's methodology, it also includes data reduction, data presentation, and conclusions. Based on the findings of research conducted by the research organization HMI Commissariat of the Faculty of Social Sciences, it can be concluded that (1) Implementation of innovative and moral organizational education, namely greeting fellow members, politeness in speaking, time discipline, internal and external mutual respect (2) Supporting factors in the implementation of innovative and ethical organizational education, namely interest, sincerity, loyalty in creating hmi organizations in creating innovative and ethical students. And the inhibiting factors for the implementation of the HMI organization in realizing innovative and moral students at the Faculty of Social Sciences Commissariat are inconsistent student attendance and different student characteristics.